Kenya's quest for democracy taming leviathan - Mutua, Makau (Boulder L. Rienner Publishers, 2008)
Tracing the trajectory of postcolonial politics, Makau Mutua maps the political forces that have shaped contemporary Kenya. He also critically explores efforts on the part of both civil society and the political opposition to reform the state. Analyzing the tortuous efforts since independence to create a sustainable, democratic state, he uses the struggle over constitutional reform as a window for understanding the larger struggles confronting Kenyan society. Mutua uses the struggle over constitutional reform as a window through which to understand the larger struggles confronting Kenyan society.
Includes bibliographical references and index.
Keywords: Constitutional history--Kenya.